2020
DOI: 10.1590/0034-7167-2020-0010
|View full text |Cite
|
Sign up to set email alerts
|

Building and validating an educational video for elderly individuals about fall risks

Abstract: Objective: to build and validate educational video for elderly individuals about fall risks. Methods: methodological study with video building. validated by 22 judges and assessed by 22 elderly individuals. Content was selected from the Fall Prevention Model and items from the Falls Risk Awareness Questionnaire. Items with an agreement greater than 0.80 were considered valid. verified through Content Validation Index (CVI) and binomial test. Results: building the video was guided by the Cognitive Theory of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 27 publications
1
10
0
7
Order By: Relevance
“…Declararam-se PcD, 45,6 milhões de pessoas no censo brasileiro (IBGE, 2010). Figuram como razões a limitação para compreensão do conteúdo dos vídeos devido ao tipo de deficiência, falta de acessibilidade comunicacional, falta de divulgação sobre a produção deles e barreiras linguísticas (Galindo Neto, 2020). É imperativo que produtores de vídeos usem ferramentas adicionais que reduzam as dificuldades vivenciadas pelas PcD e cuidadores/familiares, por meio de linguagem acessível, imagens atrativas e audiodescritivas, cores e som adequados, legendas e presença de intérprete de Libras.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Declararam-se PcD, 45,6 milhões de pessoas no censo brasileiro (IBGE, 2010). Figuram como razões a limitação para compreensão do conteúdo dos vídeos devido ao tipo de deficiência, falta de acessibilidade comunicacional, falta de divulgação sobre a produção deles e barreiras linguísticas (Galindo Neto, 2020). É imperativo que produtores de vídeos usem ferramentas adicionais que reduzam as dificuldades vivenciadas pelas PcD e cuidadores/familiares, por meio de linguagem acessível, imagens atrativas e audiodescritivas, cores e som adequados, legendas e presença de intérprete de Libras.…”
Section: Discussionunclassified
“…Os 12 princípios da Teoria orientam o planejamento e criação de multimídias para apoiar a compreensão de vídeos como forma de aprendizagem: Coerência (exclusão de imagens, palavras e sons dispensáveis); Sinalização (presença de sinais que direcionem a atenção); Redundância (uso de animação e narração ao invés de animação, narração e legenda); Contiguidade espacial (palavras e imagens correspondentes aparecem espacialmente próximas); Contiguidade temporal (palavras e imagens correspondentes aparecem ao mesmo tempo); Segmentação (informação em blocos); Pré-treinamento (apresentação geral do conteúdo antes dos detalhes); Modalidade (animação e narração ao invés de animação e texto escrito); Multimídia (uso de palavras e imagens ao invés de apenas palavras); Personalização (palavras em estilo conversacional, ao invés de estilo formal); Voz (narração com voz humana); Imagem (imagem do narrador não é imprescindível) (Sá et al, 2020).…”
Section: Metodologiaunclassified
See 1 more Smart Citation
“…They had not developed the video prior to the submission of their paper. Sá et al (2020) produced an educational video for elderly individuals about fall risks, that they validated with 22 judges, and assessed with 22 elderly individuals. They selected the content from the Fall Prevention Model (WHO, 2008), and the items from the Falls Risk Awareness Questionnaire (Lopes & Trelha, 2013), which were verified through the Content Validation Index and binomial test.…”
Section: Introductionmentioning
confidence: 99%
“…They assessed the perception of falling risk by FRAQ-Brazil (Lopes & Trelha, 2013) in the pre-test and after a 30-day follow-up. They reported that they used their video Research, Society and Development, v. 11, n. 10, e499111032333, 2022 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v11i10.32333 5 presented in a previous paper (Sá et al, 2020).…”
Section: Introductionmentioning
confidence: 99%